Effects of arbuscular mycorrhizal fungi on photosynthesis and chlorophyll fluorescence of maize seedlings under salt stress - Yan Lu, Hongwen Xu; Tong, Shuyuan (Emirates Journal of Food and Agriculture, 2018)
The impact of arbuscular mycorrhizal fungi (AMF) Glomus. tortuosum on morphology, photosynthetic pigments, chlorophyll (Chl) fluorescence, photosynthetic capacity and rubisco activity of maize under saline stress were detected under potted culture experiments. The experimental result indicated the saline stress notably reduced both dry mass and leaf area in contrast with the control treatment. Nevertheless, AMF remarkably ameliorated dry mass and leaf area under saline stress environment. Besides, maize plants appeared to have high dependency on AMF which improved physiological mechanisms by raising chlorophyll content, efficiency of light energy utilization, gas exchange and rubisco activity under salinity stress. In conclusion, AM could mitigate the growth limitations caused by salinity stress, and hence play a very important role in promoting photosynthetic capacity under salt stress in maize.